DESAIN DAN UJI COBA LEMBAR KERJA PESERTA DIDIK (LKPD) KIMIA BERBASIS PROBLEM SOLVING PADA MATERI KOLOID - Vulva - Fitrah; Arif - Yasthophi (Konfigurasi : Jurnal Pendidikan Kimia dan Terapan, 2019)
This research is motivated by the lack of understanding of students on colloidal concepts in chemistry learning and the absence of chemistry student workbook based problem solving. In this study a chemistry student workbook based problem solving design was designed to support learning in colloid lesson. It was a Research and Development (R&D) method with Borg and Gall design. This research was administrated at State Senior High School 1 Salo. Subject of this research were Media design experts, Learning lesson experts, chemistry teachers and tenth student at the tweleve grade of MIPA. Object of this research were chemistry student workbook based problem solving on colloid lesson. The instruments of this research were questionnaire of validity test by the experts and questionnaire of practicality test by teacher and students. Student workbook was good if it was valid and practice aspect quality. Validity and practicality could be seen from the result of validity and practicality by using validity and practicalities sheets. The level percentage of validity was 91.5% (Very valid) and level of practicality was 87.72% (Very practice). From the identifiy result that student workbook testing was good and practice to be an additional teaching material for teachers at school.